Elaboración del manual de seguridad y mantenimiento del laboratorio de servicios de la carrera de ingeniería en ecoturismo de la Universidad Técnica de Cotopaxi - Tapia Viteri, Marianela Roció (2013)
The objective of this manual is to instruct the user on measures of caution and care that should be under the equipment, materials and workers. For this research uses the descriptive method that allowed us to organize primary and secondary information on issues of security and maintenance of the laboratory's services. It is concluded that this document will help as a support for students, teachers and staff to enter the laboratory and handling equipment, materials to be used at the time of their internship. Finally the people expected to make use of this instruction guide has to comply with the imposed rules to prevent deterioration d equipment for a good performance and a better life.